Long COVID : The Extended Effects of the Pandemic on Labor Markets in Latin America and the Caribbean - World Bank (Washington, DC : World Bank, 2022)
More than a year on from the start of the Coronavirus (COVID-19) pandemic and with massive vaccination campaigns underway, over a quarter of the adult population in Latin America and the Caribbean (LAC) who had a job before the pandemic were still not working. Of these, over half left the labor force entirely. Women, young people, older workers, and individuals with low educational attainment levels have been disproportionately affected by this crisis. In many cases, workers have become discouraged or unable to return to work, exiting the labor market altogether. The exit of workers from the labor market was simultaneously accompanied by entry from inactivity into the labor force at unprecedented levels during the pandemic, suggesting that further examination at the country level is required to understand the role of government transfers and care work as determinants of people’s activity choices. Still, as of mid-2021, inactivity rates remained higher than before the pandemic in most countries.